Nasih Ulwan's Perspective Teacher Personality Competency in His Book Entitled Tarbiyah Al-Awlâd fî al-Islâm. - Aris Kusnadi Putra; Santi Lisnawati; Ulil Amri Syafri (al-Afkar, Journal For Islamic Studies, 2025)
Various cases of violence committed by unscrupulous teachers have spread in educational, national and social life, indicating that teachers as the main spearhead of education do not yet have a significant role in the process of building a national personality with a social and humanitarian spirit. Education undergoes a process of “dehumanization”. It is said that because education experiences a process of decline with the erosion of the human values it contains. The aim of this research is this research to analyze the concept of teacher personality competence from Nasih Ulwan's perspective in her book entitled Tarbiyah Al-Awlâd fî al-Islâm. This study uses a type of analytical descriptive qualitative research. The results of this research produce a basic concept for teachers at Madrsah Tsanawiyyah in improving personality competencies that support three other competencies, namely: first, professional competencies. Second, pedagogical competence. Third, social competence. It can be concluded that if the teacher's personality competency is carried out on an Islamic basis and in accordance with policy, then it is certain that all teachers will have reliable competence. Recommendations for the next researchers are to be able to perfect this research by examining the theoretical basis of other experts regarding personality competencies for Madrsah Tsanawiyyah teachers.